Shakespeare & Stratford - Scheil, Katherine West, 1966- (Shakespeare and, 2019)
"As the site of literary pilgrimage since the eighteenth century, the home of the Royal Shakespeare Company and the topic of hundreds of imaginary portrayals, Stratford is ripe for analysis, both in terms of its factual existence and its fictional afterlife. The essays in this volume consider the various manifestations of the physical and metaphorical town on the Avon, across time, genre and place, from America to New Zealand, from children's literature to wartime commemorations. We meet many Stratfords in this collection, real and imaginary, and the interplay between the two generates new visions of the place"--